Constructing phylogenetic tree for viral hemorrhagic fever (VHF) by RAXML - Al-Abadi, Meaad Hussein; Al-Nuaimi, Bashar Talib (Edelweiss Applied Science and Technology, 2024)
Various viruses can produce severe and frequently fatal infections known as viral hemorrhagic fevers (VHF). Comprehending the evolutionary connections among these viruses is essential for developing vaccines, treating illnesses, and conducting epidemiological surveillance. The evolutionary history and genetic relatedness of viruses that cause viral heart failure are better understood by phylogenetic research. Thus, this work aimed to undertake multiple sequence alignment and then use the Maximum Likelihood Estimate approach to produce a phylogenetic tree architecture of VHF. This study utilized 27 isolates of VHF (Ebola & Marburg) retrieved from the GenBank database (National Center for Biotechnology Information) for this investigation. The recent findings demonstrated that the Maximum Likelihood Estimate approach yielded a phylogenetic tree that was highly accurate and reliable for establishing the evolutionary relationships between VHF.